Safety and Risk Assessment of Civil Aircraft during Operation - Li, Longbiao (IntechOpen, 2020)
This book introduces safety and risk analysis methods for aircraft and aero-engines, design approaches for increasing safety and decreasing risk during operation, air traffic controllers' attitudes to mistakes hazards, theories and models of human error occurrence during aircraft maintenance processes, and damage and failure analysis for composite structures.